Arquitetura de interfaces funcionais em argilas e adobes - Juliana Calabria Azevedo (2008)
Clay is a widely used and studied material in many scientific areas. It can be called mud and it also can be used in advanced applications such as the pharmaceutical industry composites, special adsorbents etc. Adobe is basically composed of clay and it retains some of its morphological characteristics and functions. It was possible in thiswork to develop surface modifications for adobe which made the architecture of the adobe surface functional and capable of adapting to different environments and solicitations. Characteristics were studied in order to add technical features to the adobe brick: sol-gel thin films deposition at low temperatures, based mainly on TEOS, MTES and titanium IV isopropoxide (Ti4+). The selection of clays and adobe bricks was carried out considering those commercialized in the Minas Gerais region. For a better understanding of the properties of adobe, we used kaolin samples with a high degree of purity, also found in Minas Gerais. The interface modifications of interest in this study presented the following funcionalizations as goals: sol-gel hydrophobic membranes and sol-gel bactericide membranes with TiO2. The FTIR analyses for theadobe samples showed the hydrophobic effect of the MTES precursor by the absence of the free water bands in the region of 3700 cm-1 to 3600 cm-1. The hydrophobic effect of the MTES could not be observed for the kaolinite sample at same conditions (FTIR).The X-ray diffraction results for the synthesized samples with Ti4+ demonstrate that the film obtained has characteristic bands of the anatase phase. The static SIMSresults suggest the presence of the TiO2. It was possible by using the TEM to observe the double functional sol-gel membrane hydrophobic-bactericide on the adobe surface which the thickness in the range between 20 nm and 50 nm. The results demonstrate that the surface of the adobe is rough and the sol-gel membrane applied followed the topography of the surface. The double functional sol-gel membrane didnt exhibit cracks neither signs of peeling off on the surface of adobe. The adobe sample which preserved their physical integrity and apparently good attachment to the membranes were the ones coated by the hydrophobic thin films in either versions, single and double functional. After the leaching test the obtained surface roughness data, by Zygo® white light interferometer, for the functionalised adobe samples (coated)showed a decreasing of the roughness of the surface in the range of 22% to 35%